The Effectiveness of Blended Learning in Essay Writing Class for English Education Study Program - Arit, Elisabeth A; Tawarik, Oxtapianus (IKIP Siliwangi, 2025)
This study investigated the effectiveness of blended learning in improving essay writing skills among English Education Study Program students at Santo Agustinus Hippo Catholic University in West Kalimantan, Indonesia. Using an sequential experimental mixed-methods design, the study collected data from 26 third-semester students through pre-test, post-test, and semi-structured interviews. The blended learning approach applied a 30:70 ratio of face-to-face and online learning. Quantitative analysis demonstrated a substantial enhancement in students' essay writing proficiency (t = 14.392, p < 0.001), exhibiting considerable to substantial effect sizes in the introductory paragraph (Cohen's d = 1.83), concluding paragraph (d = 1.06), and paragraph unity and coherence (d = 2.53). Qualitative findings revealed that high-ability students thrived with flexibility and collaborative opportunities, while medium-ability students needed more structured guidance, and low-ability students experienced difficulties with self-regulation and technical barriers. This study suggests that blended learning can be an effective method for improving essay writing skills, even in resource-constrained environments, but requires differentiated support based on student ability levels.